(untitled) (Comprehensive Journal of Science, 2025)
This study examines the thematic diversity and its literary impact in the Maqamat of Abu al-Tahir Muhammad ibn Yusuf al-Sarqasti, considering them as a comprehensive model of Andalusian literature. The study aims to identify the types of themes addressed by al-Sarqasti, analyze how this diversity reflects the social and intellectual reality in Andalusia, and explore the relationship between the themes and the literary techniques he employed in constructing the Maqamat. The research relies on the descriptive-analytical method to examine the ninth and tenth Maqamat, complemented by a rhetorical approach to analyze stylistic devices such as saj‘ (rhymed prose), paronomasia, antithesis, simile, metaphor, and metonymy, and their relation to the conveyed meanings. Additionally, a historical approach was employed to situate the texts within their cultural and social context. The findings reveal that al-Sarqasti’s Maqamat are characterized by thematic diversity, encompassing social topics (depiction of social classes and human relationships, love and romance, literary gatherings, and public spaces) and intellectual and cultural topics (travel as a source of knowledge, literary and scholarly assemblies, analysis of values and human phenomena, and the Maqamat as a cultural and historical record). The study also demonstrates that thematic diversity is closely linked to al-Sarqasti’s literary style, as rhetorical devices are used to enhance meaning and support the aesthetic and intellectual dimensions of the texts, making them more than mere entertaining narratives or linguistic exercises, but works with cognitive, ethical, and philosophical depth. and, a comparison between Andalusian and Eastern Maqamat highlights the Andalusian Maqamat’s tendency to transcend mere cleverness toward social and intellectual analysis, reflecting the cultural specificity of Andalusia and a broader literary horizon. This confirms the importance of al-Sarqasti’s Maqamat as a valuable source for studying thought, literature, and social life in Andalusian society.